2014
DOI: 10.4236/aim.2014.413104
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Source Affects Glycolipid Production and Lipid Accumulation in the Phytopathogen Fungus <i>Ustilago maydis</i>

Abstract: When cultured in medium limited of nitrogen sources, the phytopathogen Ustilago maydis produces two amphipathic glycolipids: Ustilagic acid (UA) and Mannosylerythritol lipid (MEL), which in addition to the hydrophilic moiety, contain di-or tri-hydroxylated C16 fatty acids (UA), or C8 and C16 saturated fatty acids (MEL). We compared the growth and morphology of cells in YPD and in minimum media containing glucose and nitrogen sources such as nitrate or urea and those deprived of nitrogen. Nitrogen-starved cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…No growth and BS production was observed in the medium without any nitrogen source (nitrogen starvation) in the present study. Zavala-Moreno et al (Zavala-Moreno et al 2014) have reported that the production of glycolipids enhanced when grown in nitrogen limiting or starving conditions. According to Maneerat (2005), production of surface active compounds increases when the concentration of nitrogen depleted in the medium which is due to reduction in the activity of isocitrate dehydrogenase.…”
Section: Effect Of Carbon and Nitrogen Sources On Bs Productionmentioning
confidence: 99%
“…No growth and BS production was observed in the medium without any nitrogen source (nitrogen starvation) in the present study. Zavala-Moreno et al (Zavala-Moreno et al 2014) have reported that the production of glycolipids enhanced when grown in nitrogen limiting or starving conditions. According to Maneerat (2005), production of surface active compounds increases when the concentration of nitrogen depleted in the medium which is due to reduction in the activity of isocitrate dehydrogenase.…”
Section: Effect Of Carbon and Nitrogen Sources On Bs Productionmentioning
confidence: 99%
“…For this reason, it can be assumed that an ammonium limitation caused the itaconic acid overproduction of U. rabenhorstiana. Further, the nitrogen limitation caused the accumulation of intracellular lipid droplets, which are mostly triacylglycerols [21,34]. A secretion of cellobiose lipids and mannosylerythritol lipids in the form of needle-like crystals or oily droplets of U. maydis [20], could not be verified for U. rabenhorstiana.…”
Section: Discussionmentioning
confidence: 96%
“…In general, it is possible to generate a stable unicellular growth by deleting several genes [24]. The filamentous growth involved the accumulation of intracellular lipid droplets, which is initiated by nitrogen limitation, which in turn is needed for itaconic acid overproduction [5,19,34]. Furthermore, 89% of all fatty acids in U. rabenhorstiana were long-chain fatty acids C16:0, C18:0, and C18:2 and suggested the accumulation of triacylglycerols in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the accumulation of lipids as LDs in U. maydis under nitrogen starvation (MM-N) (Zavala-Moreno et al, 2014). Also, the dynamics of LDs under different nitrogen sources were analyzed (Romero-Aguilar et al, 2017).…”
Section: Accumulation Of Neutral Lipids In Lds Is Influenced By Nitromentioning
confidence: 99%